Study of Rainwater Potential as Raw Water Source for Campus Mosque at Engineering Faculty of Tanjungpura University - Ulli Kadaria (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Mosques need water in sufficient quantities for ablution, usually the mosques use surface water from PDAM services and well water. Surface water and ground water have decreased in quantity and quality, so it is necessary to find alternative sources of water to meet the clean water demand. On the other hand, the potential for rainwater is neglected, rainwater that falls is left to flow. Pontianak is one of the cities crossed by the equator which has high rainfall, the method of harvesting rainwater is appropriate in the tropics. This research was located on campus mosque at Engineering Faculty of Tanjungpura University. The purpose of this study was to determine the water demand in mosque and identify the potential for rainwater to meet the clean water demand in mosque. The method used in this research is field survey to calculate the water demand and interview with the mosque management to obtain supporting data. Based on the calculation, the total of water demand in mosque is 60 m3/month or 2 m3/day, while the volume of rainwater in campus mosque at Engineering Faculty of Tanjungpura University is 61.258 m3/day, and the potential volume of rainwater each month can meet the clean water demand.